Dhikr Rateeb Siribee and its Effect in Reducing Anxiety Among the MPTT-I Aceh Congregation Members - Safrilsyah, Safrilsyah; Karjuniwati, Karjuniwati; Damanhuri, Damanhuri; Suud, Fitriah M.; Subhan, Subhan; Darusman, Mhd. Ricky; Maghfirah, Wina (Universitas Islam Negeri Mataram, 2024)
The dissemination of information via social media has significantly impacted psychological issues such as stress, fear, and anxiety within society. This is exemplified by the MPTT-I congregation in Aceh, who frequently faces societal rejection regarding their dhikr practices. This study aims to evaluate the effectiveness of dhikr in alleviating anxiety among members of the Indonesian Sufism Study (MPTT-I & Dhikr Rateb Seribe). This study uses a quantitative, quasi-experimental method with a nonrandomized pretest-posttest control group design. The study involved 20 subjects, evenly divided into experimental and control groups. The data collection used the Greenberger and Padesky anxiety scale. The results indicated a significant reduction in anxiety among the MPTT-I congregation following the implementation of the Dhikr. These findings suggest that dhikr is effective in reducing anxiety within the MPTT-I & Dhikr Rateb Seribe community.